The effects of periparturient events, mastitis, lameness and ketosis on reproductive performance of Holstein cows in a hot environment - Mellado, Miguel; García, José E.; Véliz Deras, Francisco G.; de Santiago, María de los Ángeles; Mellado, Jesús; Gaytán, Leticia R.; Ángel-García, Oscar (Austral Journal of Veterinary Sciences, 2018)
The aim of this study was to determine the association among periparturient events such as mastitis, lameness (infectious and non-infectious) and ketosis and the reproductive performance of high producing Holstein cows in a hot environment. The health status and reproductive data variables were recorded from 6,566 completed lactations in a large dairy operation. A logistic regression model with the stepwise procedure was used, considering the occurrence of the health problems during the pre-breeding period as fixed effect risk factors and reproductive variables as dependent variables. Pregnancy rate of cows contracting clinical mastitis (CM) around the period of first inseminations was five percentage points lower than cows without this disease. Cows with CM shortly before or after the first service had twice the risk of requiring more than three services per pregnancy than cows with healthy udders. Cows experiencing abortion, laminitis or metritis were two times more likely to require >3 services per pregnancy than cows not experiencing these reproductive disorders. Cows experiencing lameness, mastitis and metritis presented a significantly longer interval between calving and pregnancy compared to healthy cows. Ketosis and lameness increased the odds of a cow of being inseminated for the first time after 70 days in milk. In conclusion, these results suggest that abortion, ketosis, CM, retained placenta (RP), metritis, and lameness are associated with decreased reproductive performance in high producing Holstein cows subjected to thermal stress.